Understanding Changes in Tourists' Use of Emotion Regulation Strategies in a Vacation Context. (September 2019) - Gao, Jie; Zhang, Ye; Kerstetter, Deborah L.; Shields, Stephanie
This study examines the patterns of change in tourists' use of emotion regulation strategies (ERSs) during a vacation, and their interactions with sociodemographic characteristics. Data were collected using an online survey and travel daily diaries. Repeated measures analysis of variance showed that 152 participants exhibited significant differences in their use of five ERSs with positive emotions and two ERSs with negative emotions during their travel experience, suggesting use of ERSs varies over different stages of a vacation. In addition, some sociodemographic characteristics were found to play a significant role in explaining patterns of change in tourists' use of ERSs with positive and negative emotions. These findings, which extend current emotion-based research in tourism, must be acknowledged by and incorporated into future research. Further, tourism professionals should account for the change in tourists' use of ERSs during a vacation when planning travel itineraries and programs.